Aspects Regarding the Status of Main Natural Factors and Sustainable Development in Romania - 1George UNGUREANU; 2Manuela Carmen PANAITESCU; 1Elena LEONTE; 1Eduard BOGHITA; 1Dragos Alexandru ROBU; 3Cătălin Răzvan VÎNTU (Communications of International Proceedings, 2022)
The importance of sustainable development has started to be acknowledged in Romania as well, once the various pollution sources and the restrictions affecting industrial and agricultural pollution were identified, from an economic and ecological standpoint. Sustainable development represents the need of raising awareness about environmental protection and educating people, and this aspect is reflected by the evolution of communal policies in recent years, policies marked by a shift from an approach based on constraints and sanctions to a higher level of flexibility, based on incentives. The purpose of this paper is to make a recommendation for improving existing policy by making an assessment of economic incentives in order to stimulate farmers to adopt sustainable farming systems of a viable, sustainable agriculture, capable to apply the newest technologies and lead to profit and efficiency, to the economical and organizational consolidation. To analyse the effects of different zonal packages on income of farmers and the environment a linear programming model is developed for a typical, 192 ha mixed farm in the Iasi region plain pilot area. The major activities of the farm is keeping dairy cattle, growing fodder (grass, alfalfa, silage maize) and cash crops (winter wheat and maize).
Keywords: sustainable; development; environmental; economic potential; strategy.